Studi Ikonografi Arca-Arca Jina Kṛtanāgara - Rendy Aditya Putra Ertrisia (JURNAL PANALUNGTIK, 2020)
During his lifetime, Kṛtanāgara was ordained into a number of jina statues. Previous scholarly research only focused on the Arca Mahāksobhya/Joko Dolog and the Arca Aksobhya Koleksi Museum Mpu Purwa Nomor Inventaris 89 as a statue of the ordination of Kṛtanāgara, thus closing the possibility of other jina statues. Thus this study aims to discuss the existence of several other statues as Kṛtanāgara jina, as well as the appearance of iconographic features of Buddhist monks in some Kṛtanāgara jina statues. The study began with a collection of physical descriptions through observation and evaluation of jina statues who depict Kṛtanāgara through iconographic rules. The next step is to collect supporting data in the form of ancient manuscripts and literature related to Kṛtanāgara jina. Besides that, also conduct interviews with competent speakers in their fields. The final stage is the analysis and interpretation to obtain a final conclusion. The results obtained are that Kṛtanāgara was ordained as a jina in the form of the Arca Mahāksobhya/Joko Dolog, Reco Lanang, Arca Aksobhya Koleksi Museum Mpu Purwa Nomor Inventaris 89, and Arca Pendeta Buddha Koleksi Museum Nasional Nomor Inventaris 229a. Reco Lanang represents the jina of Dhyānibuddha Kṛtanāgara while the other three statues are depictions of Kṛtanāgara as manusibuddha or highest Buddhist monks.